Understanding the role of GPs’ gut feelings in diagnosing cancer in primary care: a systematic review and meta-analysis of existing evidence - Friedemann Smith, C; Drew, S; Ziebland, S; Nicholson, BD (Royal College of General Practitioners, 2020)
Background Growing evidence for the role of GPs’ gut feelings in cancer diagnosis raises questions about their origin and role in clinical practice.